IDENTIFYING STUDENTS'NEEDS OF RELEVANT LANGUAGE SKILL MATERIALS AND FACILITIES: A NEEDS ANALYSIS OF LANGUAGE SKILLS CONDUCTED AT THE FACULTY OF LETTERS OF SOEGUAPRANATA CATHOLIC UNIVERSITY - Wuryani Hartanto; Lilik Ekawati Wijaja (Celt: A Journal of Culture, English Language Teaching & Literature, 2003)
The idea to conduct needs analysis is motivated by the rapid development in English Language which causes many demands of English ill the field of education, jobs and careers. Such development motivates the emergence of ESP ( English for Specific PUlposes) which has a great relation to the students 'jilfure jobs and careers. As a result, evel}' faculty of letters should equip its studellls with appropriate language skills, langu 1ge skill materials and facilities to prepare them infacing theirfuturejobs and careers. Based 011 such a situation. needs analysis is worth conducting ill order to find out what is actually needed by the sflldents. Severalfactors which will be explained in this study are as follows: the concept of needs. the dejlnition of needs analysis, the general ()velview about the importance of cOlldllcting needs analysis. the right time for implementing needs analysis. the contribution oflml!!,uage skills, etc. The results of all the analysis show the students' opinions 011 the language skills, I(/nguage skill /1/aterials and facilities. Therefore, they will be IIsejitlfor improving the leaching and learning processes in every faculty of letters. especiallY the Faculty or Letters Soegijapranata Catholic University.